2019
DOI: 10.1002/cav.1893
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of the affective and physiological responses induced by dynamic virtual reality environments

Abstract: Previous studies showed that virtual reality (VR) environments can affect emotional state and cause significant changes in physiological responses. Aside from these effects, inadvertently induced cybersickness is a notorious problem faced in VR. In this study, to further investigate the effects of virtual environments (VEs) with different context, three dynamic VEs were created. Each VE had a particular purpose: evoking no emotion in Campfire (CF), unpleasant emotions in Hospital (HH), and cybersickness sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…This study can be considered as the first attempt to understand and expand the body of knowledge in this field. Therefore, purposefully, like other studies of VR [42], a suite of virtual environments with distinct contexts, were created to spot any relationship. The scope of this research was limited to pleasant and horror environment genres.…”
Section: Discussionmentioning
confidence: 99%
“…This study can be considered as the first attempt to understand and expand the body of knowledge in this field. Therefore, purposefully, like other studies of VR [42], a suite of virtual environments with distinct contexts, were created to spot any relationship. The scope of this research was limited to pleasant and horror environment genres.…”
Section: Discussionmentioning
confidence: 99%
“…Our work with pupil size is an experimental evaluation of the possible utility of pupil size as a response to cybersickness. Previous studies have suggested the changes of pupil size are promising indicators of subjects' emotion [5]. But, since our study does not attempt to change subjects' emotions, if pupil size changes are observed, we will need to test whether the changes are correlated with cybersickness.…”
Section: Objective Responsesmentioning
confidence: 97%
“…Previous research has shown that symptoms of cybersickness are associated with changes in physiological measures such as heart rate, skin conductance, respiration rate, eye-blink rate, gastric tachyarrhythmia, etc. Kim et al and Cebeci et al systematically studied these changes [5,26]. The results showed that the severity of cybersickness had a significant positive correlation with heart rate, eye-blink rate, gastric tachyarrhythmia, and EEG delta waves, and a negative correlation with EEG beta waves.…”
Section: Cybersickness and Physiological Datamentioning
confidence: 99%
“…Blink rate has often been associated with negative human behaviours such as stress and fatigue [Lee et al 2010]. Furthermore, empirical studies have also suggested that changes in blink rate can also be a reliable measure for eyestrain [Cebeci et al 2019;Kim et al 2005]. Given that eye fatigue is one of the core symptoms of the SSQ [Kennedy et al 1993] it makes sense to explore this factor as a potential variable for cybersickness detection [Iskander et al 2018].…”
Section: Cybersickness and Blink Ratesmentioning
confidence: 99%